Citizens’ Adoption of an E-Health System During the Pandemic - Faye Lorraine P. Mina; Enrique B. Batara; Eucil P. Hussien; Rabby Q. Lavilles (Jurnal Studi Pemerintahan)
This study aimed to determine the factors influencing the behavioral intention of PhilHealth members to adopt My PhilHealth Portal using an extended unified theory of acceptance and use of technology (UTAUT). Variables from this theory were operationalized through indicators which were then translated into a self-reported online survey questionnaire distributed through email and Facebook. Purposive-homogeneous sampling was used to determine the sample size from the target population who are Cagayan de Oro City based PhilHealth formal economy members employed in either private or public sector. The data from the online survey was tested for reliability using IBM SPSS Statistics (version 20), and the Cronbach’s alpha (1951) coefficient was used to assess the validity of variables. To determine the causal relationship of variables on specific constructs, data were processed using licensed versions of IBM SPSS AMOS (version 26) to perform Structural Equation Modelling, which will further show the account for a specific impact of the constructs and moderating variables to behavioral intention. It is cross-sectional in nature and conducted within a short period of time. Citizens’ perceptions towards the adoption of My PhilHealth Portal can change over time as new knowledge and experiences will be accumulated. Therefore, future studies could employ a longitudinal design to obtain more accurate findings that are relevant to the general public’s adoption of government portals. Findings show that citizens’ behavioral intention to adopt My PhilHealth Portal is influenced by their trust on internet, trust on government, effort expectancy, and their perceived competence. However, the selected moderating variables appear to have no significant effect on TOI, TOG, EE, and PC to BI.